Remédiation des erreurs langagières en FLE pendant les interactions à distance à l'ENSET de l'université de Douala - Julia Ndibnu-Messina Ethé (Centre National d'Enseignement à Distance, 2016)
Web 2.0 opens paths towards a hybrid transmission of knowledge to African teachers. This hybrid teaching means an education that combines teaching in a non-virtual classroom (on site) and distance learning or a teaching that makes use of digital tools. Thus, this study aims at analyzing the written interactions and ways of remediation by tutors (teachers and assistants) on the forums for learning French. To achieve this, the analysis of educational systems of French as a foreign (TEFL) / or as second language (ESL) and distance learning at present ENSET today allows discussing the interactive activities from an educational angle. These written interactions between teachers and students of TEFL / ESL offer a dense and diverse corpus, which illustrates the recurring errors on forums for learning languages. The development of the typology of errors led to didactic proposals that could be extended to larger groups than the sample selected at HTTTC.